Association of joint exposure to various ambient air pollutants during adolescence with blood pressure in young adulthood - Jingjing Wu; Shenxin Li; Jingwen Duan; Yalan Li; Jie Wang; Peizhi Deng; Changjiang Meng; Wei Wang; Hong Yuan; Yao Lu; Minxue Shen; Qiuping Zhao (The Journal of Clinical Hypertension, 2023)
Abstract The association of various air pollutants exposure during adolescence with blood pressure (BP) in young adulthood is uncertain. We intended to evaluate the long‐term association of individual and joint air pollutants exposure during adolescence with BP in young adulthood. This cross‐sectional study of incoming students was conducted in five geographically disperse universities in China during September and October 2018. Mean concentrations of particulate matter with diameters ≤2.5 μm (PM2.5), ≤10 μm (PM10), nitrogen dioxides (NO2), carbon monoxide (CO), sulfur dioxide (SO2), and ozone (O3) at participants’ residential addresses during 2013–2018 were collected from the Chinese Air Quality Reanalysis dataset. Generalized linear mixed models (GLM) and quantile g‐computation (QgC) models were utilized to estimate the association between individual and joint air pollutants exposure and systolic blood pressure (SBP), diastolic blood pressure (DBP), and pulse pressure (PP). A total of 16,242 participants were included in the analysis. The GLM analyses showed that PM2.5, PM10, NO2, CO, and SO2 were significantly positively associated with SBP and PP, while O3 was positively associated with DBP. The QgC analyses indicated that long‐term exposure to a mixture of the six air pollutants had a significant positive joint association with SBP and PP. In conclusion, air pollutant co‐exposure during adolescence may influence BP in young adulthood. The findings of this study emphasized the impacts of multiple air pollutants interactions on potential health and the need of minimizing pollution exposures in the environment.